Natural occurrence of poly(ADP-ribosyl) histones in rat liver. - Ueda, K (1975)
Poly(ADP-ribose) bound to histones has been isolated from rat liver. When [14C]ribose was administered intraperitoneally to rats at a dosage of 300-750 mug (100-250 muCi)/10o g, approximately 1% of the radioactivity was recovered in the acid (5% CLCCCOOH)-INSOLUBLE MATERIAL OF THE LIVER NUCLEI 2 HR AFTER INJECTION. Of the acid-insoluble radioactivity, 4.5-9% was extractable with 0.25 N HCL. Carboxymethyl-cellulose column chromatography of the HCl-extracted material revealed that the radioactivity cochromatographed with histone subfractions f1 and, to a lesser extent, f2 and f3. Part of the protein-bound radioactivity was rendered acid-soluble by treatment with either snake venom phosphodiesterase or neutral NH2OH. From the enzyme digest, 5'-AMP and psiADP-ribose [2'-(5"-phosphoribosyl)-5'-AMP] were recovered, while the NH2OH treatment yielded ADP-ribose monomer and, presumably, oligomer. These observations indicate that ADP-ribose is attached to histones in vivo and is present both as a monomer and a polymer.